Measurement of city sustainability based on the grey relational analysis: The case of 15 sub-provincial cities in China. (October 2021) - Yi, Pingtao; Dong, Qiankun; Li, Weiwei; Wang, Lu
Highlights: The sustainability level of 15 sub-provincial cities in China was measured. A weighting method considering the interaction among sustainability criteria was proposed. A criteria system was built from three dimensions of Economy, Society, and Environment. Targeted suggestions were presented to promote the sustainable development of the study case. Abstract: City sustainability plays an increasingly important role in the process of rapid urbanization. Appropriate measurement of city sustainability can monitor the sustainability level and guide cities' sustainable development. This study measured the sustainability level of 15 sub-provincial cities in China from the perspective of multi-criteria decision making (MCDM). We built a criteria system from three dimensions of Economic Development, Social Progress, and Ecological Environment. A new weighting method was proposed based on the grey relational analysis, which considers the interrelationship among sustainability criteria. Then we analyzed the sustainability performance, dimensions coordination, and driving factors from the overall level, dimensional level, and criteria level. It is found that Shenzhen, Guangzhou, and Hangzhou were at a high level with measurement scores over 0.50, while Xi'an, Harbin, and Changchun were at a relatively low level with measurement scores below 0.35. The cities located in Southern and Eastern China had better performances than those in other regions. Qingdao, Shenyang, Wuhan, and Dalian showed coordinated development in the three dimensions. The population growth and tertiary industry were the key factors for the 15 cities. Finally, we discussed the measurement results and put forward targeted suggestions for the sustainable development of the cities.